The continuing enigmas of social policy - Ben Fine (United Nations Research Institute for Social Development (UNRISD), 2014)
One particular index of the systemic nature of the current crisis is the weaknesses of intellectual responses to the crisis and the inability, often self-confessed by orthodox thinkers and policy makers, to offer convincing or viable remedies. Unsurprisingly, this intellectual deficiency has primarily focused on the role of finance. But the intellectual weaknesses - especially as far as policy responses are concerned - run deeper and wider, covering (un)employment, industrial and housing policies, and so on. To a large extent, this reflects the debilitating influence of neoliberalism (looking at things in terms of a simple dichotomy between market and state, themselves simply conceived), the compromises with it, and the corresponding weaknesses of alternatives on offer prior to the crisis. These weak alternatives have swung between looking backwards to a Keynesian/interventionist renewal, and inventing alternative monikers for contemporary capitalism, such as post-Fordist or, more recently, the Cheshire-cat-grinning knowledge economy. In this light, this paper examines critically what has been one of the most successful intellectual contributions to the neoliberal period, Esping-Andersens Welfare Regimes Approach (WRA) to comparative social policy. The paper shows that the WRA has deep roots within the conditions of the post-war boom and, as a consequence, was already well past its "use by date" when it emerged in the 1990s, let alone over the subsequent two decades of neoliberalism that have been underpinned by financialization. A close examination of the literature on the WRA shows how it has suffered from being unable to account for the differences between countries and programmes and has neglected both the changing conditions associated with neoliberalism and the causal factors underpinning it, and the closer determination of social policies themselves. The paper offers similar commentary on other approaches to social policy, such as appeal to convergence, divergence or path dependence. To some degree, the study of social policy has become tired, having been used to addressing yet one more crisis of the welfare state as if all that is involved is another round of responses to neoliberal antipathy or straitened economic circumstances. With such analysis as critical point of departure - together with specification of financialization, its relationship to neoliberalism and their variegated influences over social policy - the paper offers an alternative in terms of a marriage between the developmental welfare state and (public sector) system of provision (PSSOP) approaches. More specifically, it argues that understanding of, and proposals for, social policy need to situate it in a broader developmental context. On the other hand, the paper emphasises how different elements of social policy are both country- and sector-specific in and of themselves and in relation to developmental context. This underpins the PSSOP approach that focuses upon how provision is organized for particular aspects of policy. The marriage of these two approaches is presented in contrast to other approaches already mentioned as well as by reference to World Bank postures and the current interest in conditional cash transfers.
Keywords: 330